If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2c + 3x + 5m + 4x + m = 0 Reorder the terms: 2c + 5m + m + 3x + 4x = 0 Combine like terms: 5m + m = 6m 2c + 6m + 3x + 4x = 0 Combine like terms: 3x + 4x = 7x 2c + 6m + 7x = 0 Solving 2c + 6m + 7x = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-6m' to each side of the equation. 2c + 6m + -6m + 7x = 0 + -6m Combine like terms: 6m + -6m = 0 2c + 0 + 7x = 0 + -6m 2c + 7x = 0 + -6m Remove the zero: 2c + 7x = -6m Add '-7x' to each side of the equation. 2c + 7x + -7x = -6m + -7x Combine like terms: 7x + -7x = 0 2c + 0 = -6m + -7x 2c = -6m + -7x Divide each side by '2'. c = -3m + -3.5x Simplifying c = -3m + -3.5x
| 3m+16=4m+9 | | 15p^4+8p^2=-26p^3 | | 3(x+2.05)=2x | | 9=7x+3(-4x) | | c^2-16x=x^2-2x-1 | | X=Y+W | | X+0.20X=100 | | 5x+1.5=13 | | g-23.8=4.4g | | X^2-8=10 | | X+0.15X=100 | | 4t=5t^2 | | X-VSQUARED=WSQUARED | | 4y-114=14 | | -2=-7u+3(u+2) | | 6+5(1-6x)=131 | | -4-8=-20 | | -5(2x-6)+8x= | | z^6+2z^3-6iz^3=11+2i | | 7x-5=-75 | | 6+3=27 | | -7+2=10y-7-9y | | 6x(x+9)=(2x+8)(x+9) | | 6X^2+7x=-1 | | y=2r | | x^2+2x-6ix=11+2i | | 2x+4=-5(x+5) | | -9(9x+9)+4= | | 24=2w+6(w-4) | | -4-4x=-44 | | 8(v+4)+7v=2 | | 8.35-2.5w=-4.15 |